Using Smartphone Applications to Manage Chronic Conditions in Older Adults – A Review on Level of Evidence - Tanira, Shaorin (International Journal of Human and Health Sciences (IJHHS), 2021)
Background: From health monitoring to health education and from behaviour change to falls sensing and health alerts to the simple pleasure of communication and connectedness, the mobile technologies (smartphone applications) are changing the lives of older adults. Objective: To examine current evidence of use of smartphones by older adults for health purposes (including communication, education, and health monitoring), and understand gaps and challenges in order to inform the design of future systems given the ubiquity of mobile phone technology. Methods: MEDLINE, CINAHL and Google scholar databases were searched from October 2016 to January 2017. Keywords used include ‘smartphone apps’, ‘mobile phone’, ‘chronic disease’, ‘chronic condition’, ‘older adults’ and ‘elderly’. A total of 12 articles were selected for quality assessment and grading of evidence. Results: Twelve different articles were found and categorized into nine different clinical domains with specific health related interventions. Articles were focused on diabetes care (2 articles), followed by COPD (2 articles), heart disease (1 article), Alzheimer’s/dementia Care (2 articles), osteoarthritis and pain management (1 article), fall prevention (1 article), colon cancer (1 article), palliative care (1 article), chronic kidney disease (1 article). Areas of interest studied included feasibility, acceptability, functionality and thereby determining their effectiveness. There were many different clinical domains; however, most of the studies were pilot studies. Current work in using mobile phones for older adult use are spread across a variety of clinical domains. Findings from different studies indicate that the use of mobile phone interventions has the potential to support successful management of chronic conditions and health behaviour change in older adults. Conclusion: Perceived benefits and willingness to use the smartphone apps are high; however, technical training and cost are main concerns. A common problem with elderly users was their reluctance to press buttons due to the fear of breaking something which has been resolved by touch screen technology of the smartphones. However, the advanced user clicked around the screen until he found what he was looking for, while the others spent a lot of time observing the screen and trying to determine the correct step. Promotion of user-friendly apps are expected especially for older adults having a diminished physical and cognitive abilities. International Journal of Human and Health Sciences Vol. 05 No. 04 October’21 Page: 381-387